Health Communication Methods Used by Surveillance Volunteers in COVID-19 Education during the Endemic Period (Oratio Directa, 2023)
The COVID-19 outbreak required surveillance volunteers to process data and communicate health information to communities. This qualitative study examines the health communication methods used by volunteers to educate the public. The findings identify three main methods: individual approaches, communication through community health-center teams, and communication through social media. Accurate coordination and validation are required before health information is published and consumed by the public.
Keywords: Health communication; Surveillance volunteers; COVID-19; Health education; Endemic transition